INDUKSI TUNAS DARI EKSPLAN BIJI MANGGIS (Garcinia mangostana L.) ASAL BENGKALIS SECARA IN VITRO DENGAN PERLAKUAN BAP (Benzylaminopurine) PADA MEDIUM MS - Ria Yuni Rahmawati; Mayta Novaliza Isda; Siti Fatonah (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Mangosteen (Garcinia mangostana L.) from Bengkalis island has many superiorities such as growing in the marshes and tolerant to acid soil (peat soil). In vitro culture is an alternative way to get large number and uniform mangosteen seedling. The purpose of this research was to determine the best concentration of BAP (Benzylaminopurine) in inducing mangosteen’s shoots from Bengkalis. This research used Randomized Complete block Design (RAK) with 5 concentrations of BAP (0; 1; 3; 5; 7 mg/l) with 5 replications. The result of this research showed the fastest shoot forming time and highest number of shoots present in a concentration of 5 mg / l BAP at 13 DAP and 2 shoots per explant.